Analisis Sustainability Business dan Sustainability Profitability : Studi pada Wisata Mulut Seribu Desa Daiama, Kabupaten Rote Ndao (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to analyze business sustainability and profitability sustainability at the Mulut Seribu tourist destination in Daiama Village, Rote Ndao Regency. Tourism is a strategic sector with the potential to boost the regional economy; however, the sustainability of business operations and profitability still faces various challenges. This research employs a qualitative approach supported by quantitative data. Data were collected through observation, in-depth interviews, documentation, and literature review, and analyzed using Miles and Huberman’s techniques through stages of data collection, reduction, presentation, and verification. The research informants consisted of local government officials, tourism managers, local business actors, and community members directly involved in tourism activities. The study focuses on business sustainability and profitability sustainability. The results indicate that the sustainability of Mulut Seribu tourism business has not yet been fully achieved. Economically, there are limitations in infrastructure and inadequate maintenance of facilities, affecting tourist comfort. Socially, community participation exists but is still individual-based, lacking strong formal institutions. Environmentally, conservation principles are not fully implemented, even though the area is within a conservation zone. Regarding profitability, income fluctuated significantly due to the COVID-19 pandemic, facility damage, and halted levies. Although there has been an increase in homestay rental income, long-term profitability remains unstable. These findings highlight the need for more structured management, institutional support, and synergy between the government, community, and conservation institutions to ensure that Mulut Seribu tourism can develop sustainably in terms of both business operations and profitability.